Pengaruh Sistem Informasi Akuntansi, Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada Perbankan Konvensional Di Kota Bengkulu - Oktridarti, Levy (Politeknik Raflesia Press, 2023)
The objective of this research is to know the influence of accounting information system, leadership style and motivation to the employee’s performance of conventional bank in Bengkulu City. The sample of this research were 65 employees from conventional bank in Bengkulu City. Data is collected using the instrument in the form of questionnaires. The instrument is calibrated using the validity of items and reliability coefficient. Data were analyzed using multiple regression analysis with SPSS 21. The results show that accounting information system, leadership style and work motivation has a positive and significant influence on the employee’s performance of conventional bank in Bengkulu City